Clima organizacional y desempeño laboral en la Caja Maynas agencia de la calle Arequipa Iquitos 2024 - Marichi Pereyra, Piero Alexander (2025)
The objective of the research was to determine the relationship between organizational climate and job performance at Caja Maynas, Arequipa Street branch, Iquitos, in 2024. A quantitative approach was used with a descriptive correlational design, non-experimental, and cross-sectional. The reliability of the instruments was assessed, obtaining a Cronbach's Alpha of 0.922 for organizational climate and 0.963 for job performance, indicating high reliability. The Spearman correlation results showed a coefficient of 0.598, with a bilateral significance value of 0.014, confirming a direct, moderate, and statistically significant relationship between both variables. With these findings, it is concluded that there is a direct and significant relationship between organizational climate and job performance at Caja Maynas. This study highlights the importance of a positive work environment for improving employee performance, suggesting that improving organizational climate could enhance employee performance and contribute to achieving institutional goals.